Meningkatkan Kualitas Hafalan Al-Qur’an dengan Metode Talaqqi dan Tartil di Asrama Tanwirul Qulub Desa Bangsal Kecamatan Bangsal Kabupaten Mojokerto - Nurvina Faridha Rachmawati; Muhammad A.Fulka Sa’dibih (Amaliyatu Tadris (AMYTA), 2023)
The implementation of the Talaqqi and Tartil methods aims to enable students (santri) to have specific methods for memorizing the Qur’an, thereby improving the quality of their memorization based on the rules of tajwid. In addition, these methods train students to recite the Qur’an slowly and correctly (tartil), so that Qur’anic recitation is not disorganized or rushed. This study aims to determine: (1) the quality of Qur’anic memorization before the implementation of the Talaqqi and Tartil methods; (2) the quality of Qur’anic memorization after the implementation of the Talaqqi and Tartil methods; and (3) the level of effectiveness of the Talaqqi and Tartil methods in improving the quality of Qur’anic memorization of tahfidz students at Tanwirul Qulub Dormitory, Bangsal Village, Bangsal District, Mojokerto Regency. This research is classified as Classroom Action Research (CAR). Classroom Action Research is a form of action research conducted in the classroom with the aim of improving the quality of teaching and learning practices. Based on the results of the memorization assessment records conducted by the students, the findings from Cycle I showed that before the implementation of the Talaqqi and Tartil methods, the percentage of students who achieved the minimum criteria for quality memorization did not reach 50% of the total number of tahfidz students. Out of 38 students, only a limited number met the minimum standard. After the implementation in Cycle I, the results showed an improvement, with the mastery level reaching 63.15%, equivalent to 24 students who met the criteria for quality memorization. Furthermore, the results of Cycle II showed a further increase, with 79% of students—amounting to 30 students—successfully meeting the minimum criteria for quality memorization. Based on the research findings, it is recommended that dormitory ustadzah consider continuing the implementation of the Talaqqi and Tartil methods to further improve the quality of Qur’anic memorization among tahfidz students at Tanwirul Qulub Dormitory by utilizing time as effectively as possible, considering that the Talaqqi and Tartil methods require relatively more time to implement compared to the learning methods previously applied. Penerapan metode Talaqqi dan Tartil bertujuan agar santri memiliki metode khusus dalam menghafalkan Al-Qur’an sehingga dapat meningkatkan kualitas hafalan dengan berdasarkan hukum kaidah tajwid. Serta mampu melafalkan hafalan Al-Qur’an dengan perlahan atau tartil. Sehingga tidak membuat bacaan Al-Qur’an berantakan dan tergesa-gesa. Penelitian ini bertujuan untuk mengetahui: 1) kualitas hafalan Al-Qur’an sebelum dilakukan penerapan metode Talaqqi dan Tartil. 2) kualitas hafalan Al-Qur’an sesudah dilakukan penerapan metode Talaqqi dan Tartil 3) mengetahui tingkat efektivitas metode Talaqqi dan Tartil dalam meningkatkan kualitas hafalan Al-Qur’an santri tahfidz di Asrama Tanwirul Qulub Desa Bangsal Kecamatan Bangsal Kabupaten Mojokerto. Jenis penelitian ini adalah Penelitian Tindakan Kelas (Classroom Action Research). Penelitian Tindakan Kelas adalah penelitian tindakan yang dilakukan di kelas dengan tujuan memperbaiki mutu praktik pembelajaran di kelasnya. Berdasarkan hasil rekapan nilai setoran hafalan yang dilakukan oleh santri pada siklus I menunjukkan persentase peningkatan kualitas hafalan yang pada sebelum diterapkan metode Talaqqi dan Tartil tidak sampai 50% dari jumlah santri tahfidz yakni 38 santri yang tuntas memenuhi nilai minimum kriteria hafalan berkualitas, sedangkan hasil tes di siklus I menunjukkan peningkatan dengan presentase ketuntasan kualitas hafalan di angka 63,15% dari jumlah santri yakni 24 santri tuntas memenuhi kriteria hafalan berkualitas, lalu dilanjut dengan hasil tes di siklus II yang menunjukkan peningkatan sejumlah 79% dari sejumlah 30 santri tuntas memenuhi nilai minimum kriteria hafalan berkualitas. Berdasarkan hasil penelitian, disarankan: 1) ustadzah asrama mempertimbangkan untuk melanjutkan metode talaqqi dan tartil untuk meningkatkan kualitas hafalan santri tahfidz di Asrama Tanwirul Qulub dengan memanfaatkan waktu yang semaksimal mungkin, dikarenakan metode talaqqi dan tartil dalam pelaksanaannya membutuhkan waktu yang relatif lebih lama dari pembelajaran yang biasa diterapkan selama ini..